2014
DOI: 10.18388/abp.2014_1839
|View full text |Cite
|
Sign up to set email alerts
|

A severe recessive and a mild dominant form of Charcot-Marie-Tooth disease associated with a newly identified Glu222Lys GDAP1 gene mutation.

Abstract: Charcot-Marie-Tooth (CMT) disease caused by mutations in the GDAP1 gene has been shown to be inherited via traits that may be either autosomal recessive (in the majority of cases) [CMT4A] or autosomal dominant [CMT2K]. CMT4A disease is characterized by an early onset, and a severe clinical course often leading to a loss of ambulation, whereas CMT2K is characterized by a mild clinical course of benign axonal neuropathy beginning even in the 6th decade of life. Clinical data from a GDAP1 mutated patient suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Sanger sequencing showed that the three family members are heterozygous ( Fig. 1b) for this previously described pathogenic mutation [1]. These MFN2 and GDAP1 variants are absent from the dbSNP and ExAC databases.…”
mentioning
confidence: 77%
“…Sanger sequencing showed that the three family members are heterozygous ( Fig. 1b) for this previously described pathogenic mutation [1]. These MFN2 and GDAP1 variants are absent from the dbSNP and ExAC databases.…”
mentioning
confidence: 77%
“…Intriguingly GDAP1 has been involved both in axon-related disease CMT2K (Cassereau et al, 2011) and myelinrelated disease CMT4A (Kabzińska et al, 2014), suggesting that mitochondria of both glia and axons are involved. Moreover mutations in OPA1 (optic atrophy 1), a gene essential for mitochondria fusion, were recently shown to give rise to systemic neurodegeneration including a peripheral neuropathy with features of axonal degeneration and demyelination (Bonneau et al, 2014;Yu-Wai-Man et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a regulator of mitochondrial fission and there is abundant evidence associating alterations of this gene to the hereditary Charcot‐Marie‐Tooth neuropathy (CMT). Different mutations of this gene have been observed and linked to different clinical manifestations of CMT . Some mechanisms involving changes in mitochondrial movement, abnormal distribution, and perturbations in mitochondrial fission in CMT have been associated with mutations of GDAP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Different mutations of this gene have been observed and linked to different clinical manifestations of CMT. 31,32 Some mechanisms involving changes in mitochondrial movement, abnormal distribution, 33 and perturbations in mitochondrial fission 34 in CMT have been associated with mutations of GDAP1. Our results may provide a starting point for further exploration of therapies targeting mitochondrial processes, 35 which might have beneficial effects in the treatment of DIPN.…”
Section: Discussionmentioning
confidence: 99%